New records of Euglenophyceae for Bangladesh - Gani, Md. Ataul; Alfasane, Md. Almujaddade; Khondker, Moniruzzaman (Bangladesh Journal of Plant Taxonomy, 2012)
Eight newly recorded species of Euglenophyceae from Bangladesh have been illustrated and described in the present paper. The species are Euglena fundoversata L.P. Johnson, E. korshikovii Gojdics, E. minuta Prescott, E. sacculiformis Schiller, Lepocinclis truncata Da Cunha, Phacus pusillus Lemn., P. strongylus Pochm. and P. wettsteini Drez. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10945 Bangladesh J. Plant Taxon. 19(1): 85-88, 2012 (June)